Answer:
Option (b) and (d) are correct.
b) [tex]32m^4+12m^3=4m^3(8m+3)[/tex]
d) [tex]40m^6-4=4(10m^6-1)[/tex]
Step-by-step explanation:
Given: Some statement
We have to check which statements are true.
We will check all one by one.
Consider
a) [tex]15m^3-6m=3m(5m^2-6m)[/tex]
Consider the Left hand side of the given statement,
[tex]15m^3-6m[/tex]
Taking 3m common from each term, we have,
[tex]15m^3-6m=3m(5m^2-2m)[/tex]
Thus, LHS ≠ RHS
Thus, the statement is false.
b) [tex]32m^4+12m^3=4m^3(8m+3)[/tex]
Consider the Left hand side of the given statement,
[tex]32m^4+12m^3[/tex]
Taking [tex]4m^3[/tex] common from each term, we have,
[tex]32m^4+12m^3=4m^3(8m+3)[/tex]
Thus, LHS = RHS
Thus, the statement is True.
c) [tex]6m^2+18m=6m^2(1+3m)[/tex]
Consider the Left hand side of the given statement,
[tex]6m^2+18m[/tex]
Taking 6m common from each term, we have,
[tex]6m^2+18m=6m(m+3)[/tex]
Thus, LHS ≠ RHS
Thus, the statement is false.
d) [tex]40m^6-4=4(10m^6-1)[/tex]
Consider the Left hand side of the given statement,
[tex]40m^6-4[/tex]
Taking 4 common from each term, we have,
[tex]40m^6-4=4(10m^6-1)[/tex]
Thus, LHS = RHS
Thus, the statement is True.
Thus, Option (b) and (d) are correct.